Herbert i jego tłumacz - Chojnowski, Przemysław (Postscriptum Polonistyczne, 2020)
The article presents literary friendship between the poet and Karl Dedecius – the first and most important translator of his poetry into German. The article is an introduction into their voluminous correspondence. Letters that present Dedecius’ efforts aimed at anchoring Herbert’s creativity into German language and rising in it related literature, reveal for us the figure of the poet and his halfemigrant condition. The article discusses Herbert’s poem Colantonio – S. Gierolamo e il Leone, poem dedicated to his German translator. Saint Jerome presented in the poem is a patron and a symbol of perfection for translators. He is distinguished not only through his titanic work, but above all through his attitude based on openness and courage.